Magnetic perforation: Why we say NO to kids - Aishath Azna Ali; Anil Dhungana; Mohamed Kamel Sobhi Mohamed; Ali Zaadhee; Raya Rasheed; Abdulla Ubaid; Xin Leh Lee; Firdaus Hayati; Khasnizal Abd Karim; Andee Dzulkarnaen Zakaria (Journal of Pediatric Surgery Case Reports, 2023)
Foreign body (FB) ingestion is common among children. It is alarming when it is a magnetic foreign body as it can cause interloop attraction resulting in perforation, fistulas and or volvulus. This case report presented 2 cases of magnetic FB ingestion by children. The first child had a history of FB ingestion and presented with signs and symptoms of intestinal obstruction. The parents of the second child gave no history of FB ingestion which might have caused the delay in diagnosis and treatment. The FB ingestion was confirmed by abdominal radiography in both cases and the patient recovered well after the reparation of perforation sites in an exploratory operation.